(untitled) (Research, Society and Development, 2020)
Today, the State of Ceará (Brazil) appears on the national and international scene as a reference for educational quality, alluding to the policy of professional education integrated with high school. In the academy, it is a consensus that education is related to factors that can define implications of school success or failure. Considering aspects related to motivation, this article aimed to identify and discuss the presence of this factor for quality educational provision. To this end, a qualitative study was carried out, with a descriptive nature, in the form of a comparative study, carried out through bibliographic survey, documentary research, on-site observation and semi-structured interviews, among 10 professional schools that offer this integrated education modality. to high school, in the State of Ceará, 5 with high performance (44 subjects) and 5 with low performance (39 subjects), based on the results of external evaluations. The study confirms the need for motivation in school environments and in the development of pedagogical work, while contributing to scientific and professional training, in addition to conceiving theoretical contributions to the construction of new research to improve learning.